2022
DOI: 10.1111/jocs.16910
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19, ECMO, and respiratory infection: A new triad?

Abstract: In December 2019, the initial outbreak of COVID-19 started in Wuhan, China, which rapidly escalated to an international scale within weeks. 1 This ultimately resulted in it being declared as a global pandemic by the World Health Organization (WHO) in March 2020. 2 This highly contagious respiratory infection has since mutated and evolved to enable viral survival in the host. 3 Treatment pathways for the virus have also changed and improved, accompanied by more knowledge of the disease pathogenesis. For example… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…For severe acute respiratory distress syndrome (ARDS), prone ventilation for 16 hours/day is suggested 79 . Additional rescue interventions include extracorporeal membrane oxygenation (ECMO) 80 , 108 , 109 .…”
Section: Introductionmentioning
confidence: 99%
“…For severe acute respiratory distress syndrome (ARDS), prone ventilation for 16 hours/day is suggested 79 . Additional rescue interventions include extracorporeal membrane oxygenation (ECMO) 80 , 108 , 109 .…”
Section: Introductionmentioning
confidence: 99%
“… 9 A study by Shih et al demonstrated a higher rate of secondary coinfections in COVID‐19 positive patients with ARDS following extracorporeal membrane oxygenation placement, suggesting limited benefit of this rescue therapy. 10 This advocated for a standardized and documented approach to manage an ATAAD, where evidence is slowly growing on the optimal surgical approach, such as on the efficacy of valve‐sparing root replacement in ATAAD repairs. 11 A study from Wang et al alternatively provided insight into the use of triple branched stent graft implantation for ATAAD.…”
mentioning
confidence: 99%
“…For example, SARS‐CoV‐2 infection has shown to exacerbate arrhythmias, acute coronary syndrome, and thromboembolism 9 . A study by Shih et al demonstrated a higher rate of secondary coinfections in COVID‐19 positive patients with ARDS following extracorporeal membrane oxygenation placement, suggesting limited benefit of this rescue therapy 10 . This advocated for a standardized and documented approach to manage an ATAAD, where evidence is slowly growing on the optimal surgical approach, such as on the efficacy of valve‐sparing root replacement in ATAAD repairs 11 .…”
mentioning
confidence: 99%